Sea-change : negotiating the United Nations Convention on the Rights of Persons with Disabilities - a New Zealand perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Policy at Massey University, Palmerston North, New Zealand - Roe, Sinéad (Massey University, 2014)
The United Nations Convention on the Rights of Persons with Disabilities (CRPD) was the first human rights convention of the 21st century. It was notable because of the high levels of involvement stakeholders – disabled people – had in the negotiations process. This project looks at the role played by the disabled New Zealanders in the New Zealand delegation to the Ad Hoc Committee considering the text for the CRPD. It examined to what extent the disability rights movement slogan ‘nothing about us, without us’ was reflected in this process. Through interviews with disabled people who had represented NGOs, national human rights institutions and disabled people’s organisations at the UN, it finds that disabled people were instrumental in drafting a convention that addressed real-life human rights issues for disabled people. Using Stienstra’s (2003) framework for assessing the effectiveness and value of consultation process, it also finds that CRPD negotiations show how the involvement of stakeholders in consultation processes can greatly enhance both the process itself and the results. The process represents a sea-change in terms of how consultations with disabled people should be conducted. With genuine interest and willingness to listen to the lived experience of disability, governments have much to gain from genuine engagement with disabled people and their representative organisations. The implications for social policy are shown to demonstrate how ‘nothing about us, without us’ can move beyond being a mere slogan. When correctly applied during consultations, it can become a transformative and powerful guiding principle for policymakers and legislators alike.
Keywords: People with disabilities; Convention on the Rights of Persons with Disabilities and Optional Protocol (2007 March 30); Human rights; Stakeholder consultation; Social policy; New Zealand